Alteration of mRNA abundance, oxidation products and antioxidant enzyme activities during oocyte ageing in common carp Cyprinus carpio - Mohagheghi Samarin, Azin; Mohagheghi Samarin, Azadeh; Østbye, Tone-Kari Knutsdatter; Ruyter, Bente; Sampels, Sabine; Burkina, Viktoriia; Blecha, Miroslav; Gela, David; Policar, Tomas (PloS one, 2019)
Oocyte ageing is the most important factor affecting egg quality of several fish species after ovulation. Oxidative stress has been proposed as the initiator of the oocyte ageing process in other vertebrates. To identify the role of oxidative stress and apoptosis on the progress of oocyte ageing in the common carp Cyprinus carpio, changes in the relative mRNA abundance of selected transcripts were examined. The possible alteration in the oxidation status of the oocytes during ageing was also studied. In addition, the activity of antioxidant enzymes during oocyte ageing was evaluated. Oocytes from 6 females were incubated in vivo for 14 hours post-ovulation (HPO) and in vitro for 10 hours post-stripping (HPS) at 20°C before fertilization. Hatching rates were over 65% up to 4-6 HPO, finally dropping to 1.3% at 12-14 HPO.Hatching rates were over 65% up to 4-6 HPO, finally dropping to 1.3% at 12-14 HPO. Hatching rates were more than 70% for the eggs stored in vitro up to 6 HPS and then decreased to 21.3% at 10 HPS. The results demonstrated no significant changes in the relative mRNA levels of oxidative stress-related genes or genes involved in the cell cycle during the progress of oocyte ageing in common carp. Additionally, the amount of TBARS and carbonyls did not change as time elapsed following ovulation. The apoptosis-related genes however, were significantly altered following the prolonged time interval between ovulation and fertilization. The lack of response of both activities of antioxidant enzymes and oxidation products during oocyte ageing strengthens the conclusion that oxidative stress is unlikely to be a main factor determining the progress of oocyte ageing in common carp. However, an increase in the mRNA abundance of apoptosis-related genes demonstrates that apoptotic pathway might be involved in the progress of oocyte ageing.
Keywords: stárnutí buněk; RNA, Messenger; antioxidancia; rybí proteiny; oocyty; Oxidoreductases; Fish Proteins; kapři; Cellular Senescence; oxidoreduktasy; oxidace-redukce; Animals; ženské pohlaví; Antioxidants; zvířata; Carps; Oxidation-Reduction; Female; messenger RNA; Oocytes